El Derecho de la Innovación: una especialización legal en auge - Fernandini, Claudia; Saavedra, Yajaira (Pontificia Universidad Católica del Perú, 2025)
Innovation Law in Peru has become a fundamental legal specialization to promote economic and social development in a constantly changing technological environment. This interdisciplinary field seeks to create a legal framework that encourages investment in research, development and innovation, facilitating transfer technology and knowledge between universities and companies. Although intellectual property protection drives the creation of new products, the country faces challenges such as regulatory fragmentation and lack of institutional coordination.Initiatives such as SINACTI, PROCIENCIA and PROINNOVATE seek to improve the coordination of the innovation ecosystem. However, barriers still persist, such as the low culture of innovation and the need for specialized lawyers.

El Derecho de la Innovación en Perú se ha convertido en una especialización legal fundamental para impulsar el desarrollo económico y social en un entorno tecnológico en constante cambio. Este campo interdisciplinario busca crear un marco jurídico que fomente la inversión en investigación, desarrollo e innovación, facilitando la transferencia de tecnología y conocimiento entre universidades y empresas. Aunque la protección de la propiedad intelectual impulsa la creación de nuevos productos, el país enfrenta desafíos como la fragmentación normativa y la falta de coordinación institucional. No obstante, el marco legal peruano enfrenta importantes desafíos, como la fragmentación normativa y la falta de coordinación entre instituciones. Iniciativas como SINACTI, PROCIENCIA y PROINNOVATE buscan mejorar la articulación del ecosistema de innovación. Sin embargo, aún persisten barreras como la baja cultura de innovación y la necesidad de abogados especializados.
The Law of Innovation: a legal specialization on the rise
Keywords: Law of Innovation; Economic development; Intellectual property; Technology transfer; Innovation ecosystem; Research and development; Derecho de la Innovación; Desarrollo económico; Propiedad intelectual; Transferencia de tecnología; Ecosistema de innovación; Investigación y desarrollo; https://purl.org/pe-repo/ocde/ford#5.05.00